Communication between patients with obstructive sleep apnoea syndrome and healthcare personnel during the initial visit to a continuous positive airway pressure clinic. Issue 3 (7th November 2016) - Broström, Anders; Fridlund, Bengt; Hedberg, Berith; Nilsen, Per; Ulander, Martin
Abstract : Aims and objectives: To describe facilitators and barriers from a patient perspective in communications between patients with obstructive sleep apnoea syndrome and healthcare personnel during the first meeting when continuous positive airway pressure is initiated. Background: Adherence to continuous positive airway pressure treatment tends to be poor, especially at the initial phase of treatment. Communication between the patient and healthcare personnel has not been studied from the patient perspective, as either a barrier or facilitator for adherence. Methods: A descriptive design using qualitative content analysis was used. Interviews with 25 patients with obstructive sleep apnoea syndrome took place after their initial visit at four continuous positive airway pressure clinics. A deductive analysis based on The 4 Habits Model (i.e. emphasise the importance of investing in the beginning of the consultation, elicit the patient's perspective, demonstrate empathy and invest in the end of the consultation) was conducted. Results: Building confidence (i.e. structure building, information transfer, commitment) or hindering confidence (i.e. organisational insufficiency, stress behaviour, interaction deficit) was associated with investing in the beginning. Motivating (i.e. situational insight, knowledge transfer, practical training) or demotivating (i.e. expectations, dominance and power asymmetry, barriers) was associated with eliciting the patient's perspective. Building hope (i.e. awareness, sensitivity, demonstration of understanding) or hindering hope (i.e. unprepared, uncommitted, incomprehension) was associated with showing empathy. Agreement (i.e. confirmation, responsibilities, comprehensive information) or disagreement (i.e. structural obscurity, irresponsibility, absent‐mindedness) was associated with investing in the end. Conclusions: Understanding of facilitators and barriers, as described by patients, can be used to improve contextual conditions and communication skills among healthcare personnel. Relevance to clinical practice: A patient‐centred communication technique should be used in relation to all stages of The 4 Habits Model to facilitate shared decision‐making and improve adherence to continuous positive airway pressure treatment.